Interpretation of Irish Nationalism in The Shaughraun by Dion Boucicault , John Bull’s Other Island by George Bernard Shaw, and Translations by Brian Friel - Nima Mohammad, Shaima (Opción, 2019)
The study discusses interpretation of Ireland in three Irish dramas : The Shaugh- raun , John Bull’s Other Island , and Translations. The introduction presents Ireland and the political vision which the Irish playwrights have been discussing through- out history. The Irish drama produces new and different versions of Irishness by interpreting the Irish stage. Selected scenes are taken from each play and then ana- lyzed as far as the subject is concerned. Discussion and analysis start with The Shaughraun by Dion Boucicault ,then John Bull’s Other Island by George Bernard Shaw , and finally Translations by Brian Friel. Each play is presenting the impor- tance of understanding and interpreting Ireland on stage. Such interpretation and understanding can be attained in showing the difficult circumstances that Ireland suffer from. Political disputes and conflicts for national identity are used by the Irish playwrights as the main themes in their drama. Finally , the study ends with the conclusion which sums up the success of the three dramas in interpreting Ire- land in view of politics and nationalism as well.